The role of computed tomography in evaluation of the early signs of acute ischemic stroke - Vojinović, Radiša; Opancina, Valentina D (Medicinski časopis, 2017)
A stroke is a sudden loss of brain function which happens due to the disruption of cerebral blood flow. It is characterized by expeditious development of clinical symptoms during first few minutes or hours after which symptoms progress and in some patients lead to death. In more than 80% of patients with stroke, the cause is vascular insufficiency and this type of stroke is called ischemic. It is an emergent condition which needs accelerated management so that optimum care and prognosis can be reached. Evaluation of the ischemic stroke is managed with noncontrast computed tomography in most cases, thanks to its widespread avalability. A detailed literature search through the Medline and Ebsco databases was performed, using the following terms: (computed tomography) AND (acute ischemic stroke) AND (early signs).We selected original investigations, meta-analyses and reviews from the past 10 years, with accessible full-texts, in the English language, as well as significant reference lists of articles which could contribute to the readers’ comprehension. After detailed review of the literature, we have segregated and described following early signs in acute ischemic stroke: insular ribbon sign, obscuration of the lentiform nucleus, hyperdense artery sign, hemispherical sulcal effacement and focal hypoattenuation. . These signs are related to consequences of cellular hypoperfusion and cytotoxic oedema. The aim of this paper was to review the literature regarding the role of computed tomography in patients with early signs of acute ischemic stroke and to serve as an educational material that illustrates those findings.